Developing Intercultural Communicative Competence in an Haitian Creole language acquisition program in Chile - Sumonte, Valeria (Íkala, Revista de Lenguaje y Cultura, 2020)
This article aims to describe the results of a Haitian Creole language acquisition program, looking to foster intercultural communicative competence among Chilean officers, and favor migrant inclusion. The program, based on the intercultural communicative competence, had a duration of 50 hours, beginning with three sessions that present what the migration process means, the country of origin of the migrants, delivered by migrants, who then become linguistic mediators, and several linguistic aspects of Spanish and Haitian Creole languages. Data on the results of the program were collected through an interview and a language skills test, administered to the participants, to officers from the Investigation Police, and to health care practitioners, at the end of its implementation. The results show that the program favors the link between individuals from different cultural backgrounds, since it relies upon the exchange of participants having equally valued knowledge, and promotes the participation of learners in managing their learning and anticipating the context they will face. This facilitates the inclusion of migrant people, speaking a different language from that of the host society, which gives them a greater likelihood to successfully insert themselves in labor, educational and cultural settings.